Phytogenic Bioactive Compounds Shape Fish Mucosal Immunity - Firmino, Joana P.; Galindo-Villegas, Jorge; Reyes-López, Felipe E.; Gisbert, Enric (Frontiers in Immunology, 2021)
Aquaculture growth will unavoidably involve the implementation of innovative and sustainable production strategies, being functional feeds among the most promising ones. A wide spectrum of phytogenics, particularly those containing terpenes and organosulfur compounds, are increasingly studied in aquafeeds, due to their growth promoting, antimicrobial, immunostimulant, antioxidant, anti-inflammatory and sedative properties. This trend relies on the importance of the mucosal barrier in the fish defence. Establishing the phytogenics’ mode of action in mucosal tissues is of importance for further use and safe administration. Although the impact of phytogenics upon fish mucosal immunity has been extensively approached, most of the studies fail in addressing the mechanisms underlying their pharmacological effects. Unstandardized testing as an extended practice also questions the reproducibility and safety of such studies, limiting the use of phytogenics at commercial scale. The information presented herein provides insight on the fish mucosal immune responses to phytogenics, suggesting their mode of action, and ultimately encouraging the practice of reliable and reproducible research for novel feed additives for aquafeeds. For proper screening, characterization and optimization of their mode of action, we encourage the evaluation of purified compounds using in vitro systems before moving forward to in vivo trials. The formulation of additives with combinations of compounds previously characterized is recommended to avoid bacterial resistance. To improve the delivery of phytogenics and overcome limitations associated to compounds volatility and susceptibility to degradation, the use of encapsulation is advisable. Besides, newer approaches and dedicated methodologies are needed to elucidate the phytogenics pharmacokinetics and mode of action in depth.